Evaluasi Tingkat Kepuasan Pelanggan Terhadap Pelayanan Cafe A Day Hoper Menggunakan Metode Kano - Claodio, Antoni; Fitriani, Risma; Momon, Ade (Fakultas Teknik Universitas Tulang Bawang, 2026)
The increasingly competitive culinary industry requires businesses to continuously improve service quality to ensure customer satisfaction and loyalty. Cafe A Day Hoper, located in Karawang, West Java, needs to identify which service attributes are most important to customers. This study aims to quantitatively evaluate customer satisfaction using the Kano model. A descriptive quantitative method was applied through a structured questionnaire distributed to 51 respondents. The data were analyzed using Kano’s evaluation matrix to classify service attributes into five categories: Must-be (M), One-dimensional (O), Attractive (A), Indifferent (I), and Reverse (R). The results showed that 14 out of 20 attributes (70%) were categorized as Must-be, indicating basic service expectations that must be fulfilled. Meanwhile, 3 attributes (15%) were categorized as One-dimensional, 1 attribute (5%) as Attractive, and 2 attributes (10%) as Indifferent. No attributes fell into the Reverse category. These findings indicate that most customer satisfaction at Cafe A Day Hoper depends on the fulfillment of essential service elements, while certain attributes have the potential to significantly enhance satisfaction if improved. Therefore, the cafe is advised to prioritize improving Must-be and One-dimensional attributes while developing Attractive features as competitive differentiators. Keywords: Attribute Classification, Customer Satisfaction, Kano Method, Service